Long Night of the Tankers Hitler's War Against Caribbean Oil - Bercuson, David J. (Beyond Boundaries, 2014)
Long Night of the Tankers presents a fresh account of a lesser-known but critical component of the Atlantic naval theatre during World War II. Using war diaries, after-action reports, and first-hand accounts, authors Bercuson and Herwig examine the story behind Operation Neuland, the German plan to interrupt vital oil supplies from reaching the United States and the United Kingdom by preventing Allied oil tankers from leaving refineries in the Caribbean. The story begins in February 1942 and follows this German attempt to scuttle the Allied war machine through to the end of the war. Told largely from the German perspective, it details the planning and execution of the Germans and the diplomatic, political, and military responses of the Allies, particularly the United States, to overcome the German effort. Winner, 2014 John Lyman Book Award for U.S. Naval History (North American Society for Oceanic History)